Determinan Audit Report Lag Pada Perusahaan Sektor Energi Yang Terdaftar Di BEI - Ade Nugra Sahbanta Ade Nugra Sahbanta; Meutia Dewi; Tuti Meutia (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
This study intends to discuss the factors that influence Audit Report Lag in energy sector companies listed on the Indonesia Stock Exchange. This research was conducted at Energy Sector Companies Listed on the Indonesia Stock Exchange using secondary data obtained from published company financial reports. The data analysis method used is multiple linear regression and uses a statistical tool, namely SPSS (Statistical Product And Service Solutions) software. The results of the study show that firm size has a significant effect on audit report lag, leverage has a significant effect on audit report lag, independent commissioners have no significant effect on audit report lag, audit committee has no significant effect on audit report lag and firm size, leverage, independent commissioners and committees simultaneous audits have a significant effect on audit report lag.